Information search, integration, and personlization : 11th International Workshop, ISIP 2016, Lyon, France, November 1-4, 2016, Revised selected papers /: 11th International Workshop, ISIP 2016, Lyon, France, November 1-4, 2016, Revised selected papers. (2017) - Unknown
No abstract available